Fostering bidirectional trainee-led partnerships through a technology-assisted journal club – The GASOC experience. (January 2022) - Ravi, Krithi; Nkuliza, Delphine; Patel, Reema; Niyitegeka, Joseph; Davidson, Sarah; Aruparayil, Noel
Since 2017, the Global Anaesthesia Surgery and Obstetric Collaboration (GASOC) has been hosting journal clubs to promote critical appraisal of global surgery publications. The COVID-19 pandemic has prompted a transition to an online-only journal club format. Attendees have rated the online GASOC journal clubs highly in terms of relevance for their learning and development, and the ability to engage with discussions. This transition has allowed more trainees in low- and middle-income countries (LMICs) to register for journal clubs, but barriers have continued to restrict their participation. Feedback submitted by participants has allowed GASOC to identify and address these barriers in order to promote bidirectional partnerships between high-income country and LMIC trainees.